DIRECTOR'S EXPERTISE, EXECUTIVE'S EXPERTISE, AND FIRM LEVERAGE IN MANUFACTURING INDUSTRY: EVIDENCE FROM TWO-TIER BOARD SYSTEM IN INDONESIA - Nugraha, Adri Putra; Soewarno, Noorlailie (Jurnal Aplikasi Manajemen, 2022)
This empirical research analyzes the director's and executive's expertise on the leverage of Indonesian manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018. Ordinary Least Squares were used to answer the research problems and test the hypotheses. The leverage was measured using Total Short-Term Debt (STD), Total Long-Term Debt (LTD), and Total Debt in Book Value (TDBV). At the same time, the director's and executive's expertise is proxied by postgraduate and professional degrees in finance or accounting. This study finds that a director's professional degree in finance or accounting influences leverage by LTD but does not significantly affect leverage proxied by TDBV and STD. Then, an executive's postgraduate degree significantly impacts leverage proxied by TDBV and STD but does not significantly influence leverage proxied by LTD. Furthermore, the director's postgraduate degree and executive's professional degree in finance and accounting do not affect leverage in all proxies. In control variables, significant influences were found in the effects of firm size on LTD and STD, profitability proxied by ROA on LTD, profitability proxied by ROE on STD, and growth on LTD. Meanwhile, firm age, Non-Debt Tax Shield (NDTS), Earnings Volatility (EVO), and Tangibility (Tang) do not affect leverage in all proxies.